Diagnostic yield of diagnostic yield of polyp-adjacent biopsies for patients with inflammatory bowel disease: A cross-sectional study - Lahiff, C; Wang, L; Travis, S; East, J (Oxford University Press, 2018)
IntroductionPatients with inflammatory bowel disease (IBD) undergoing polypectomy are recommended by current guidelines to have biopsies taken from adjacent mucosa to determine whether there is dysplasia present. With improvements in endoscopic imaging it is now possible to characterise colonic lesions with higher levels of confidence than previously. We reviewed the diagnostic yield of polyp-adjacent biopsies in IBD. Materials and MethodsA systematic search of our histopathology database revealed cases where polyps had been endoscopically resected or biopsied in patients with IBD. Endoscopy reports and medical records were reviewed, patient demographic and disease-specific details were recorded, along with details of polyp characteristics and histopathology outcomes. ResultsThree hundred and two polyps were biopsied or resected in 131 patients undergoing 178 colonoscopies. Median polyp size was 4mm (range 1-45) and the predominant morphology was Paris 0-Is (n=98, 32%). Histology was tubular adenoma in 76 (25%), tubulovillous adenoma in 14 (5%), hyperplastic in 112 (37%), post-inflammatory in 32 (11%), sessile serrated polyp in 31 (10%), traditional serrated adenoma in 2 (0.7%), flat high-grade dysplasia or cancer in 2 (0.7%) and other in 33 (11%). Dysplasia in adjacent biopsies was detected in 2 patients (0.7%), which was endoscopically visible in both cases. The proportion of endoscopically unsuspected dysplasia was 0/300 (0%, 95% CI 0-1.6%). ConclusionThe diagnostic yield for polyp-adjacent biopsies in patients with IBD is negligible. With high definition technology and chromoendoscopy it may no longer be necessary to biopsy endoscopically normal adjacent tissue to detect invisible dysplasia.